Influence of Impeller Geometry on the Unsteady Flow in a Centrifugal Fan: Numerical and Experimental Analyses. (21st January 2008) - Younsi, M.; Bakir, F.; Kouidri, S.; Rey, R.
Abstract : The aim of this study is to evaluate the influence of design parameters on the unsteady flow in a forward-curved centrifugal fan and their impact on the aeroacoustic behavior. To do so, numerical and experimental studies have been carried out on four centrifugal impellers designed with various geometrical parameters. The same volute casing has been used to study these impellers. The effects on the unsteady flow behavior related to irregular blade spacing, blade count and radial distance between the impeller periphery and the volute tongue have been studied. The numerical simulations of the unsteady flow have been carried out using computational fluid dynamics (CFD) tools based on the unsteady Reynolds averaged Navier Stokes (URANS) approach. The study is focused on the unsteadiness induced by the aerodynamic interaction between the volute and the rotating impeller blades. In order to predict the acoustic pressure at far field, the unsteady flow variables provided by the CFD calculations have been used as inputs in the Ffowcs Williams-Hawkings equations (FW-H). The experimental part of this work concerns measurement of aerodynamic performance of the fans using a test bench built according to ISO 5801 (1997) standard. In addition to this, pressure microphones have been flush mounted on the volute tongue surface in order to measure the wall pressure fluctuations. The sound pressure level (SPL) measurements have been carried out in an anechoic room in order to remove undesired noise reflections. Finally, the numerical results have been compared with the experimental measurements and a correlation between the wall pressure fluctuations and the far field noise signals has been found.